Diet therapy with fodmaps restriction has benefits in fibromyalgia - Marum, Ana Paula (2016)
The effects of a diet restriction in FODMAPs (Fermentable oligo-di-monosaccharides polyols) is being studied on the symptoms of Fibromyalgia (FM) and its impact on quality of life (QOL) besides the effect on gastrointestinal (GI) symptoms. High prevalence of functional GI disorders is found in FM and Low FODMAP Diet has growing scientific evidence as IBS (Irritable Bowel Syndrome) therapy.